A framework to diagnose the causes of river ecosystem deterioration using biological symptoms. Issue 11 (6th September 2020) - Feld, Christian K.; Saeedghalati, Mohammadkarim; Hering, Daniel
Abstract: River assessments are predominantly based on biological metrics and indices selected or designed to integrate the impact of multiple causes of deterioration (stressors) operating at various spatial scales. Yet, the integrative nature of many bioassessment systems does not allow for tracing back individual stressors and their influence on the overall assessment result. Thus, river managers often fail to link bioassessment with programmes of management measures, to improve ecological quality. Here, we present a novel diagnostic approach that allows to estimate the probability of individual stressors being causal for biological degradation at the scale of individual riverine ecosystems. Similar to medical diagnosis, we use various symptoms (macroinvertebrate metrics) and probabilistically link them to various potential causes of ecological status degradation (stressors). Symptoms and causes are informed by a training dataset of 157 samples (stressors, taxa lists) from central European lowland rivers and are linked through a Bayesian network (BN). Three separate BNs addressing three different spatial scales (catchment, reach and site) are presented. Water quality‐related causes are most influential at the catchment scale, while hydromorphological causes prevail at finer scales. Causes indicating riparian degradation are most influential at the reach scale. Many symptoms show strong linkages to causes and reveal ecologically meaningful relationships, thus pointing at the potential diagnostic utility of the symptoms selected. BNs are validated using an independent dataset of 47 samples. Overall, model accuracies range 53%–58% for the three BNs, while for individual nodes (causes and symptoms) up to 100% concordance of predicted and actual node states in the validation data is achieved. The BNs are implemented as interactive online diagnostic tools to allow end users an easy application. Synthesis and applications . Bayesian inference can greatly assist the diagnosis of potential causes of ecosystem deterioration based on a selection of diagnostic biological metrics. If integrated into a Bayesian network, symptoms and potential causes can be linked and inform management decisions on appropriate measures, to improve biological and ecological status. Diagnostic Bayesian networks thus support end users bridge the gap between biological monitoring and appropriate programmes of management measures. Abstract : Bayesian inference can greatly assist the diagnosis of potential causes of ecosystem deterioration based on a selection of diagnostic biological metrics. If integrated into a Bayesian network, symptoms and potential causes can be linked and inform management decisions on appropriate measures, to improve biological and ecological status. Diagnostic Bayesian networks thus support end users bridge the gap between biological monitoring and appropriate programmes of management measures.